2018
DOI: 10.2340/00015555-2827
|View full text |Cite
|
Sign up to set email alerts
|

Pain Quality Assessment Scale for Epidermolysis Bullosa

Abstract: Pain is one of the most debilitating symptoms in epidermolysis bullosa (EB) leading to reduced quality of life. Pain in EB comprises both neuropathic and non-neuropathic qualities. An assessment of pain qualities has not formerly been completed in EB. The Pain Quality Assessment Scale (PQAS) is an adjusted version of the validated Neuropathic Pain Scale and includes 20 pain qualities and descriptors. Patients with EB (n = 43) rated the pain qualities in the PQAS on 20 numerical scales and 1 multiple choice que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
1
20
0
3
Order By: Relevance
“…Pain in EB significantly impacts quality of life and day‐to‐day functioning . In addition to nociceptive pain associated with blistering and wounds, peripheral nerve damage objectified in RDEB, and postulated in JEB, adds plausibility to reported high pain scores in these EB types . Neuropathies limit the central role of opioids for EB pain as they may be less effective for this type of pain according to systematic analysis …”
Section: Discussionmentioning
confidence: 99%
“…Pain in EB significantly impacts quality of life and day‐to‐day functioning . In addition to nociceptive pain associated with blistering and wounds, peripheral nerve damage objectified in RDEB, and postulated in JEB, adds plausibility to reported high pain scores in these EB types . Neuropathies limit the central role of opioids for EB pain as they may be less effective for this type of pain according to systematic analysis …”
Section: Discussionmentioning
confidence: 99%
“…The burden of pain and itch was reported in seven studies [53,54,[57][58][59][60][61], 5 of which utilized patient-reported outcome measures (PROMs, Table 5) [53,[57][58][59][60]. Patients with RDEB reported high levels of pain and pruritus compared to patients with DDEB, epidermolysis bullosa simplex (EBS), and other skin diseases [53,[57][58][59][60].…”
Section: Pain and Itchmentioning
confidence: 99%
“…The burden of pain and itch was reported in seven studies [53,54,[57][58][59][60][61], 5 of which utilized patient-reported outcome measures (PROMs, Table 5) [53,[57][58][59][60]. Patients with RDEB reported high levels of pain and pruritus compared to patients with DDEB, epidermolysis bullosa simplex (EBS), and other skin diseases [53,[57][58][59][60]. In a US survey study, patients with RDEB (N = 32) ranked the top three most bothersome symptoms to be skin lesions and blisters (7/32 [23%]), itching (5/32 [16%]), and pain (5/32 [16%]) [61].…”
Section: Pain and Itchmentioning
confidence: 99%
See 2 more Smart Citations